Assessment Of Proximate And Mineral Composition Of Twenty Edible Fishes Of Parangipettai Coastal Waters - G.MARICHAMY; M.A.BADHUL HAQ; R.VIGNESH; V.SEDHURAMAN; A.R.NAZAR (International Journal of Pharma and Bio Sciences, 2012)
The measurement of some proximate profiles such as protein contents, lipids and moisture contents in fish by products is often necessary to ensure that they meet the requirements of food regulations in nutrition aspects and commercial specifications. Minerals are essential nutrients, they are components of many enzymes and metabolism, and contribute also to the growth of the fish. The human body usually contains small amount of these minerals and the deficiency in these principal nutritional elements induces a lot of malfunctioning; as it reduces productivity and causes diseases. Fish received increased attention as a potential source of animal protein and essential nutrients for human. It should be considered that fish tissue presents elevated nutritional significance and therefore is a particularly optional dietary module. The objective of this work was to analyze the proximate and mineral composition of twenty edible fishes of parangipettai coast.